HUBUNGAN PENGETAHUAN DENGAN TERJADINYA SPRAIN DAN STRAIN PADA PEMAIN SEPAK BOLA PERSIBO 1949 - AZIZAH, FIDROTIN; MAFTHUKHIN, AHMAD (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2016)
ABSTRACT             Sprain and sprain is a form of injury to the musculoskeletal system. Soccer player is a high risk of sprains and strains experienced events. Lack of knowledge in the handling of influential players sprain and strain. The purpose of this study identify "relations with the knowledge sprains and strains in soccer players in the team Persibo 1949.This research uses the analytical method, cross-sectional approach. The entire population of football players Persibo 1949 2014, totaling 27 people. The sample totaled 27 people. Using a non-probability sampling technique that is total sampling. Collecting data using a questionnaire. Analysis of data with crosetab, editing, coding, scoring, tabulating, presented in tables and percentages and curve.The results showed that the relationship of knowledge with the sprain and strain on Persibo soccer players in 1949 can be explained that of the 27 respondents, 17 respondents (63%) had sufficient knowledge never experienced sprain and strain.The conclusion is more than most of the football players in 1949 Persibo have enough knowledge about sprains and strains, majority of the respondents had experienced sprains and strains, and knowledge There is a relationship with the occurrence of sprains and strains in soccer players Persibo 1949 Keywords: Knowledge, sprains and strains, soccer players, and Persibo 1949